THE EFFECTIVENESS OF THE MODELING METHOD IN TEACHING TECHNIQUES IN THE TYPES OF WRESTLING (International Scientific Journal Alfraganus, 2024)
The article presents ways to optimize the teaching of technical methods in wrestling. Themethod of modeling the teaching of technical methods in the training of wrestling types wasstudied. A survey questionnaire was used among trainers about the effective use of modelingmethods of training processes. In wrestling, it differs from other sports due to the fact that theathlete's technical movements are many and varied. The classification, system and terms ofwrestling techniques have been developed to regulate the technical actions of a wrestler and tocreate an opportunity for communication between specialists in this field.
Keywords: Physical training, tactical methods, training, training process, modeling, optimization.